The Mediating Role of Organizational Culture in the Relationship between Work Motivation, Professional Responsibility, and Teacher Performance - Nurdiana Nurdiana; Mesiono Mesiono; Muhammad Fadhli (Newinera Publisher, 2026)
This study examines the mediating role of organizational culture in the relationship between work motivation, professional responsibility, and teacher performance among 165 public junior high school teachers in Kota Kisaran, Indonesia. Using path analysis, the research tested direct and indirect effects within a structural model based on organizational behavior theory. Results revealed that organizational culture significantly mediates the influence of both work motivation and professional responsibility on teacher performance, transmitting 42.4% of each variable's total effect. While all three predictors demonstrated significant direct effects on performance, organizational culture emerged as the strongest predictor (β = 0.561, p < 0.001), explaining 47.4% of performance variance. The simultaneous model achieved robust explanatory power (R² = 0.484, F = 50.295, p < 0.001) with perfect model fit (Q = 1.00). These findings demonstrate that teacher performance results from synergistic interactions between individual characteristics and organizational contexts rather than isolated factors. The study contributes to educational management literature by empirically validating culture as a critical transmission mechanism linking motivation and accountability to professional outcomes. Implications suggest that school leaders should prioritize integrated interventions addressing motivation, responsibility, and culture simultaneously rather than fragmented approaches to enhance teaching quality effectively.